Penguatan Literasi Membaca Siswa Melalui Pendampingan Pembelajaran Dengan Memanfaatkan Media Kartu Bergambar - Sa'diyah, Animastus; Syarif, Nor Cholida; Oktaviani, Halida; Fatir, Akhmad; Sumo, Maimon (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2024)
Student literacy skills are very important because they influence student academic achievement. So far, the literacy skills of students from disadvantaged groups who live in rural areas and suburbs are very low. This international community service aims to increase student literacy among students living in rural areas such as remote areas or on the outskirts of urban areas by utilizing picture card media. This service was carried out in Kuala Lumpur, Malaysia using the mentoring method. There are 16 students involved in international community service activities from classes 1 and 2. The service activity consists of four stages, the first stage is introduction and socialization, the second stage is observation, the third stage is the application of picture card media, the last stage is evaluation. International commonity service has enabled students who previously had difficulty pronouncing letters and words to successfully articulate both. This community service can be declared successful according to the goal, because it can increase students’ literacy, especialy in reciting the alphabet and reciting word with the help of picture card media.